Unlocking the Digital Age The Musician's Guide to Research, Copyright, and Publishing - DeLaurenti, Kathleen; Copland, Andrea I. (Open textbook library., 2024)
Based on coursework developed at the Peabody Conservatory, this book serves as a crucial resource for early career musicians navigating the complexities of the digital era. This guide bridges the gap between creative practice and scholarly research, empowering musicians to confidently share and protect their work as they expand their performing lives beyond the concert stage as citizen artists. It offers a plain language resource that helps early career musicians see where creative practice and creative research intersect and how to traverse information systems to share their work. As professional musicians and researchers, the authors’ experiences on stage and in academia makes this guide an indispensable tool for musicians aiming to thrive in the digital landscape.